Personality beliefs as a predictor of smartphone addiction (Archives of Clinical Psychiatry, 2019)
Objective: The purpose of this study is to determine the relation between smart phone addiction and personality beliefs of university students. Methods: A total of 1007 students, 637 females (63.3%) and 370 males (36.7%) participated in the study. “Smart phone addiction scale short form” was used to measure smart phone addiction and “personality beliefs scale” was used to identify personality beliefs. Results: According to the performed multiple regression analysis, it was found out that dependent, antisocial, narcissist, histrionic, borderline, paranoid personality, schizoid personality, obsessive compulsive personality, passive-aggressive personality and avoidant personality beliefs predicted smart phone addiction at significant level (R = 0.38, R2 = 0.15, p < 0.001). The mentioned variables explain 15% of the variance. An examination of the t-test shows that dependent personality (t = 5.585, p < 0.001), passive-aggressive personality (t = -4.485, p < .001) and paranoid personality (t = 2.901, p < .01) belief among the mentioned variables are a significant predictor of smart phone addiction. Discussion: The obtained results show that dependent, passive-aggressive and paranoid personality beliefs are a significant predictor of smart phone addiction. Research findings are discussed in the light of relevant literature.